Archaeological survey of the sites in the northeastern part of Zadar County (In situ, 2024)
The paper presents preliminary results of an archaeological reconnaissance of sites from the wider area of Benkovac, Gračac, Novigrad, Obrovac and Posedarje was carried out, led by the author of these lines. In this spacious part of Zadar County, there are numerous archaeological sites, most of which have not been explored until now. They belong to different periods, from prehistory to the early Modern Period.
Keywords: archaeological survey; Benkovac; Gračac; Novigrad; Obrovac; Posedarje